Ready to Do OpenCourseWare? A Comparative Study of Taiwan College Faculty - Wei, Huei-Chuan; Chou, Chien (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2021)
This study aimed to address the teaching readiness issues of OpenCourseWare (OCW). Specifically, the research goal was to examine Taiwanese college faculty members’ level of teaching readiness for OCW via a questionnaire named “Teaching Readiness Scale for OCW” (TRS-OCW). A total of 142 Taiwanese college faculty members both with and without OCW teaching experience participated in this study. The results showed that faculty members with OCW teaching experience had significantly higher readiness levels in the factors of perception of administrative support, personal characteristics, and OCW recognition when compared to faculty members without OCW teaching experience. Male faculty members with OCW teaching experience had higher readiness than female faculty members with OCW teaching experience in the OCW recognition factor. Moreover, the job position of OCW-experienced faculty did not make a difference in any readiness factor. Finally, perceived administrative support was the only significant predictor of the willingness of college faculty without OCW teaching experience to provide OCW in the future.